Analysis Of The State Financial Losses To Subsidiaries Of State-Owned Enterprises In Terms Of Business Judgment Rules - Fajar Reyhan Apriansyah (Eduvest - Journal of Universal Studies, 2024)
The recovery of financial losses suffered by subsidiaries should prioritize recovery efforts that have a non-punitive nature or without punishing a certain person who is considered responsible for the management of BUMN subsidiaries unless there is intentional unlawful conduct and there are elements of criminal acts in it. In accordance with the principle of business judgment rule, the directors can be exempted, because the directors are considered to have made business decisions in accordance with good faith. In this research, the author uses a descriptive analytical research method, because the author will describe or provide an overview of the object under study through the data collected. The form of research used in this writing is normative legal research, because this research uses legislation and court decisions and also legal norms that exist in society. Researchers also collect data in the form of decisions from the corruption court on corruption cases that harm state finances. Losses arising in subsidiaries of SOEs whose capital is not sourced from the state budget or is not equity participation of SOEs and does not receive or use state facilities, are not included in the State's losses. the role of the business judgment rule if the person commits acts of criminal acts of corruption not due to encouragement or coercion and/or business decisions that are not based on prudence from the directors, the directors will be free from legal liability.